OPTIMALISASI KOMBINASI BUDIDAYA IKAN LELE (Clarias sp) DAN PATIN (Pangasius pangasius) DI DESA KURO TIDUR KECAMATAN ARGAMAKMUR KABUPATEN BENGKULU UTARA - Mujiarto, Avif; Nusril, Nusril; Mulyasari, Gita (Jurnal AGRISEP, 2015)
Research titled optimization combination cultivation of fish catfish (Clarias sp) and patin (Pangasius pangasius) in the Kuro Tidur Village Subdistrict Argamakmur North Bengkulu Regency, aims to understand the large income levels and combination cultivation of catfish and patin fish in the pool belonging to Mr. Azmi Nur in the Kuro Tidur Village subdistrict Argamakmur North Bengkulu Regency condition steady and profit maximum. The determination of location and respondents in this research is deliberately (purposive) that is a unit of the business of cultivating fishes belonging to Mr. Azmi Nur located in the Kuro Tidur Village Subdistrict Argamakmur North Bengkulu Regency, with the business owners produces product more than one, which is kinds of fish catfish and patin fish. Instrument the analysis used is income analysis and linear programming analysis to know the optimal fish combination and give benefits maximum. After analyzed the results of operating income cultivation of fish belonging to Mr. Azmi Nur in 10 months production activities is Rp 1.061.610.350,02. With contribution of income from production of fish catfish Rp 528.553.700,00 and patin fish Rp 533.056.650,02. And a combination of optimal within 10 months production to cultivation of catfish is 15220,29 square meters and not cultivate patin fish, contributing margin maximum Rp 1.527.393.000,-. Resources overgrowth is broad pond 779,7139 square meters and 9075,394 working hours labor. As for resources any excess can economy is broad the pool of 779,7139 square meters and working hours jobs for 9075,394 hours.